Validation of a multivariable prediction model for post‐engraftment invasive fungal disease in 465 adult allogeneic hematopoietic stem cell transplant recipients. Issue 5 (8th March 2019) - Rodríguez‐Veiga, Rebeca; Montesinos, Pau; García, Estefanía; Boluda, Blanca; Rojas, Rafael; Serrano, Josefina; Martínez‐Cuadrón, David; Martín, Carmen; Sanz, Jaime; Tabares, Salvador; Piñana, José L.; Lorenzo, Ignacio; et al.
Summary: Background: Recently, we reported a simple prognostic score for post‐engraftment invasive fungal disease (IFD) obtained in 404 adult allogeneic hematopoietic stem cell transplant (alloSCT) (training cohort). Objectives: We aim to validate this score in an external cohort assessing the 1‐year cumulative incidence (CI) of post‐engraftment IFD. Additionally, we analyse the type of IFD and incidence of IFD according to type of prophylaxis. Patients/methods: We included 465 consecutive adult recipients surviving >40 days who engrafted and were discharged without prior IFD (median age 45 years, range, 14‐69). Results: Patients classified as low‐risk, 139; intermediate‐risk, 162; and high‐risk, 164 (35% vs 27% in the training cohort, P = 0.03). The CI of probable/proven IFD in the validation cohort was 8% vs 11% in the training cohort ( P = 0.006). The only voriconazole prophylaxis used in the training cohort was 100 mg/12 h, 65% vs 27% in the validation cohort, but 38% received 200 mg/12 h. Thus, the validation cohort showed a lower CI of IFD ( P = 0.009). The post‐engraftment IFD score was validated, showing a CI of IFD for low‐, intermediate‐ and high‐risk of 3%, 6% and 14%, respectively ( P < 0.001). Conclusion: To our knowledge, this is the first prognostic index to predict the occurrence of post‐engraftment IFD after alloSCT that has been validated in an external cohort.